Aquatic Humic Substances: Relationship Between Origin and Complexing Capacity - Jesus Gonzalez-Guadarrama, Maria de; Aurora Armienta-Hernandez, Ma; Rosa, Andre H. [UNESP] (Springer, 2018)
Aiming to determine the relationship between source and complexing capacity, humic substances obtained from three sites (Sorocaba and Itapanhau Brasilian rivers, and Xochimilco Lake in Mexico) were studied. Copper, manganese, zinc and arsenic complexing capacity were determined for the three substances under various pH conditions. Results showed similar complexing capacity for the three elements depending on the chemistry of each one and on the physico-chemical conditions. Speciation diagrams showed that these conditions affect both, the humic substances, and the transition metals and arsenic.
Keywords: Aquatic humic substances; Complexation; Transition metals; Arsenic; pH; Redox